Information: The Oil in the Wheel of National Development - Asamoah-Hassan, Helena R. (Ghana Library Journal, 2003)
Libraries playa major role in the educational system, the development of a strong human resource base and the socioeconomic and political progress of every country. Libraries also satisfy the recreational needs of a nation’s citizenry. To turn out sound products at every level of education, there is the need for the teacher and the taught to have access to resources to enhance their goals. One of the main resources is the libra ry. Again, the underlying factor of any nation’s development is instructive knowledge in all facets of life. If knowledge is un-harnessed, it is no knowledge. It is the library which collects, organises, preserves and makes such knowledge available as and when needed. The library is also a means by which people can improve their status in life, with little formal classroom education. Libraries can therefore be seen as the oil in the wheel of national development.